A finite element perturbation method for the prediction of rockburst - Sharan, S.K. (Computers & structures, 2007)
A finite element model is proposed to predict the potential occurrence of rockburst in underground openings. It is assumed that rockburst results due to instability of rock mass and the analysis is based on a perturbation technique. The rock mass is considered to be elastic-brittle-plastic. A novel method of elastic supports is used to simulate the effects of unbounded rock mass. Mohr-Coulomb and Hoek–Brown failure criteria are used and both associated and non-associated plasticity are considered. The effectiveness and efficiency of the proposed numerical technique are demonstrated by comparing finite element results with analytical solutions for ‘deep’ circular openings in rock mass subject to hydrostatic in situ stress. Analyses of example problems are presented to demonstrate the potential occurrence of rockburst predicted by using the proposed model.